Warum ist 3 * ln (x) = ln (x ^ 3)?

Warum ist 3 * ln (x) = ln (x ^ 3)?
Anonim

Antworten:

Verwenden Sie die Definition des Logarithmus und der grundlegenden Eigenschaften von Exponenten.

(Details unten)

Erläuterung:

Grundlegende Definition:

#color (weiß) ("XXX") ln (a) = b # meint # e ^ b = a #

Lassen #s = 3 ln (x) #

#color (weiß) ("XXX") rArr ln (x) = s / 3 #

#color (weiß) ("XXX") rArr ^ (s / 3) = x #

#color (weiß) ("XXX") rArr-Wurzel (3) (e ^ s) = x #

#color (weiß) ("XXX") rArr ^ s = x ^ 3 #

#color (weiß) ("XXX") rArrln (x ^ 3) = s #

#color (weiß) ("XXX") rArrln (x ^ 3) = 3ln (x) #